2017
DOI: 10.1038/srep42181
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Characteristics of Polymer-Based Low Ice Adhesion Surfaces

Abstract: Ice adhesion is mainly dictated by surface properties, and water wettability is frequently correlated with ice adhesion strength. However, these established correlations are limited to high ice adhesion and become invalid when the ice adhesion strength is low. Here we carried out an experimental study to explore the relationships between low ice adhesion strength and room temperature surface properties. A variety of room temperature properties of 22 polymer-based hydrophilic and hydrophobic samples consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 53 publications
4
103
0
Order By: Relevance
“…It was concluded that increased hardness of the coatings was not the cause of rising τ ice . This agreed with the findings of He et al, who reported no correlation between the room temperature hardness of a material and ice adhesion . Surface topography was then examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM).…”
Section: Resultssupporting
confidence: 89%
“…It was concluded that increased hardness of the coatings was not the cause of rising τ ice . This agreed with the findings of He et al, who reported no correlation between the room temperature hardness of a material and ice adhesion . Surface topography was then examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM).…”
Section: Resultssupporting
confidence: 89%
“…The VST is very common due to its simple and economical set-up and performance, although the location of the force probe impacts the ice adhesion strength greatly [32], and the stress distribution may not be completely uniform [8,17,18]. The VST is commonly in use by several research groups [7,11,[32][33][34][35][36][37][38][39], and has been attempted as a standard for ice adhesion measurement utilizing only commercially available instruments [14]. When comparing reported ice adhesion strengths, it is also necessary to include the type of ice tested.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the traditional high‐energy consumption de‐icing strategies (i.e., electrothermal de‐icing and vibratory de‐icing), functional materials inspired from natural biological surfaces mightily appeal to many researchers to develop an anti‐icing method without energy consumption by mimicking the plant surface topographies . As well known, the famous Lotus Effect is widely used and induces to construct the hierarchical topography of composite micro‐nanostructures in favor of entrapping more air pockets to repel water and finally realize the aim of preventing ice accumulation . Also, many theoretical and experimental studies have been reported that the trapped air pockets play a thermal insulation role in preventing the freezing of supercooled water, and cause a remarkable reduction in solid/liquid contact area .…”
Section: Introductionmentioning
confidence: 99%
“…As well known, the famous Lotus Effect is widely used and induces to construct the hierarchical topography of composite micro‐nanostructures in favor of entrapping more air pockets to repel water and finally realize the aim of preventing ice accumulation . Also, many theoretical and experimental studies have been reported that the trapped air pockets play a thermal insulation role in preventing the freezing of supercooled water, and cause a remarkable reduction in solid/liquid contact area . The resultant situation is that triggering ice nucleation gets more difficulty due to the increasing energy barrier, finally showing a certain extent of icing‐delay performance .…”
Section: Introductionmentioning
confidence: 99%